Potential evolution of the renewable hydrogen sector using California as a reference market. (1st February 2023) - Reed, Jeffrey; Dailey, Emily; Shaffer, Brendan; Lane, Blake; Flores, Robert; Fong, Amber; Samuelsen, Scott
Highlights: Dispensed cost of hydrogen projected to reach cost parity by mid 2020s creating condition for self-sustainability. Biomass-to-hydrogen assessed to be least-cost in the 2020s at roughly 2/kg but electrolytic ultimately becomes least cost. Renewable hydrogen has the potential to be a cost-effective approach to decarbonization in multiple sectors. Massive construction program needed to meet potential demand. Significant government support needed to ensure sector scaling. Abstract: This paper describes a multi-element analysis to assess least-cost approaches to scaling the renewable hydrogen sector to support deep decarbonization of applications requiring energy dense, transportable, and storable fuel. The analysis uses California as a reference market. The focus of the analysis is understanding the resource potential and cost evolution of renewable hydrogen dispensed as vehicle fuel (the anchor source of demand) and determining the feasibility and timing of achieving fuel cost parity with conventional fuels adjusting for fuel-economy. The analysis is novel in that is fully cross-sectoral on the demand side and multi-technology and spatially resolved at the facility level on the supply side. Production technology shares are assessed based on relative cost of produced hydrogen including feedstock constraints. Technology costs are benchmarked and projected using both secondary sources and primary analysis. The sectoral demand forecast is based on a combination of quantitative and qualitative assessment of cost competitiveness with alternative decarbonization strategies. The overall conclusion is that, with appropriate policy support, the RH2 sector can reach self-sustainability (price point at parity with conventional fuel on a fuel-economy adjusted basis) by the mid to late 2020s. The analysis also brings into focus the massive construction program needed to scale the renewable hydrogen sector at a regional scale.